Excreta silage for maintaining pregnant cows and heifers - McKee, M.; Conway, K.L.; Fink, G.; Kimple, K.; Hoover, J.D.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Preliminary trials the summer of 1975 tested the value of excreta silage for maintain pregnant cows and heifers. Ingredients in the excreta silage were wheat straw, cattle excreta, corn, and molasses. Eighty mature cows were divided into three lots and received either excreta silage, alfalfa haylage, or ½ excreta silage and ½ alfalfa haylage as sources of roughage for 59 days (July 25 to September 22). Cows receiving excreta silage tended to gain more than cows on haylage or ½ haylage and ½ excreta silage. Twenty-nine, sixteen-month old, pregnant, part Simmental heifers were divided into two lots. One group received excreta silage the other, haylage, as roughage for 52 days (July 25 to September 15). Their gains did not differ significantly.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Silage; Cows; Heifers; Haylage